A volcano under China's Great Wall. (November 2016) - Mason, Roger
Abstract : Cone sheets are rare in China but are found in the Houshihushan sub‐volcanic Ring Complex (HRC) near the town of Shanhaiguan, Hebei Province. The HRC rises above a narrow coastal plain as the Houshihushan mountain massif (Fig.1 ) in a scenic region about 400 km ENE of Beijing by the Bohai Gulf, where the Great Wall reaches the sea. It has a discontinuous outer ring‐dyke of porphyritic quartz syenite, separated from an inner stock of alkaline granite by a discontinuous screen of pyroclastic rocks down‐faulted to the present erosion level by caldera subsidence. The pyroclastic rocks, which have similar petrographic and geochemical characteristics to intrusive rocks of the ring‐dyke, cone‐sheets and central stock, were erupted from the same volcano and subsequently foundered during caldera subsidence.